Students' attitudes towards reading for pleasure in Universiti Teknologi MARA Sarawak / Affidah Morni - Morni, Affidah (2008)
This study investigates students' attitudes towards reading for pleasure. Also, this study tries to discover the relationship between reading materials and reading environment on one hand and students' attitudes towards reading for pleasure on the other. The subjects of the study consisted of 98 students who represented Part 3 and Part 4 Bachelor Degree students from three different faculties. There were two types of instruments used to collect the data, namely the questionnaires and the semistructured interview. Ninety eight questionnaires were distributed to the respondents and 10 students were interviewed. The results from the study were very encouraging. The study revealed that most respondents possessed positive and encouraging reading attitudes towards reading. Most respondents were able to value reading not only for academic purposes but also for pleasure. They perceived reading as a relaxing, fun and enjoyable activity. Though most respondents put a high value on reading, many of them failed to decide whether they are active readers or not which may be due to their inconsistencies in reading. With regard to reading materials, it was discovered that most respondents agreed that the choice and characteristics of the reading materials contributed to their attitudes towards reading. According to them, reading materials that appeal to their needs and interests will create a pleasurable reading experience for them. However, some interesting discoveries from the study were majority of the respondents were unable to decide whether technical texts would make them lose interest in reading. The findings also featured that the reading environment had a great influence on the students' attitudes towards reading for pleasure. Teachers, parents, peers and the learning institution are among the motivating factors discovered to have encouraged the students to commit themselves to reading for pleasure. On the other hand, most respondents believed that their reason for reading was not exclusively due to their teacher's reading act. From the correlation analyses, it was also gathered that the reading materials and reading environment had a strong influence on the students' attitudes towards reading for pleasure. On a different note, the correlation analyses showed some negative relationships between types of reading materials and average hours students spent on reading. Apart from that, some implications gathered from the findings also featured that some students might not practice what they believed even though they were aware of the importance of reading. In fact, some of them mostly spent their time reading for academic purposes rather than for pleasure. Attention should also be given on the authenticity of the reading materials as most respondents were unable to decide whether they found enjoyment reading materials that were not of their choice. Due to that, it is pertinent that teachers, parents, and stakeholders look into these implications seriously and find proactive ways in tackling the matter. In a nutshell, students read for pleasure when they find reading to be an enriching activity, which is very much supported by the reading materials and the reading environment.